Insights on adaptive and innate immunity in canine leishmaniosis. Issue 1 (20th April 2016) - HOSEIN, SHAZIA; BLAKE, DAMER P.; SOLANO-GALLEGO, LAIA
SUMMARY: Canine leishmaniosis (CanL) is caused by the parasite Leishmania infantum and is a systemic disease, which can present with variable clinical signs, and clinicopathological abnormalities. Clinical manifestations can range from subclinical infection to very severe systemic disease. Leishmaniosis is categorized as a neglected tropical disease and the complex immune responses associated with Leishmania species makes therapeutic treatments and vaccine development challenging for both dogs and humans. In this review, we summarize innate and adaptive immune responses associated with L. infantum infection in dogs, and we discuss the problems associated with the disease as well as potential solutions and the future direction of required research to help control the parasite.